(untitled) (Huellas, 2016)
The study of modern infrastructure networks in terms of "large technical systems" was firstly established by Hughes and later developed by social analysts of technology such as Joerges, Mayntz and Gras. Milton Santos incorporated notions from this area of knowledge when he characterized the current technical system and the geographical space. The article reviews the concept of large technical system, emphasizing a set of contributions that are highly useful in the field of geography, i.e. insights likely to be integrated at the moment of space theorizing. The basis for organizing conceptual articulations is present in Milton Santos’ theory of space. So, the ideas discussed are reinterpreted applying a theoretical framework that foresees a particular understanding of the nature of the geographical element. The contributions, therefore, aimed at providing a conceptual background to approach the structure, operation and development of large technical systems: heterogeneous, complex, diversified and highly political creations that play strategic roles in the modernization of society, involved in virtually all human practices and which define their own space.